Stability and median rationalizability for aggregate matchings - Federico Echenique; SangMok Lee; Matthew Shum; M. Bumin Yenmez (Games, 2021)
We develop the theory of stability for aggregate matchings used in empirical studies and establish fundamental properties of stable matchings including the result that the set of stable matchings is a non-empty, complete, and distributive lattice. Aggregate matchings are relevant as matching data in revealed preference theory. We present a result on rationalizing a matching data as the median stable matching.
Keywords: 330; aggregate matching; lattice; median stable matching; rationalizability